Isolation of a cDNA clone for the gamma subunit of the chloroplast ATP synthase of Chlamydomonas reinhardtii: import and cleavage of the precursor protein. - Yu, L M (1988)
A cDNA library from Chlamydomonas reinhardtii, constructed in the phage expression vector lambda gt11, was probed with antiserum directed against the nuclear-encoded gamma subunit of the chloroplast H+-transporting ATP synthase [ATP phosphohydrolase (H+-transporting) or chloroplast coupling factors 0 and 1, EC 3.6.1.34] of C. reinhardtii. A cDNA was isolated and transcribed in vitro. The transcript was translated in vitro and immunoprecipitated with anti-gamma-subunit serum to yield a product that coelectrophoresed with the immunoprecipitated product from in vitro-translated polyadenylylated RNA. These proteins were larger than the mature gamma subunit, either immunoprecipitated as chloroplast coupling factor 1 or as the individual subunit. Thus, the gamma subunit is synthesized as a precursor of greater molecular weight in C. reinhardtii. Furthermore, the precursor protein encoded by the cDNA is imported into pea chloroplasts and processed to a lower molecular weight polypeptide that coelectrophoreses with mature C. reinhardtii gamma subunit. The largest cDNA isolated is about the same length as the corresponding mRNA (approximately equal to 1900 bases long) and probably contains the entire coding region. Southern blot analyses revealed restriction fragment length polymorphisms and that the gamma subunit is probably encoded by an intron-containing single-copy gene.